The awareness of Islamic financial planning among UMK students - Nurul Nazhirah Zailan; Nurul Shafika Abd Gahni; Nurul Syahida Ahmad; Nurul Syamimie Idayu Abdullah (2023)
This study focuses on religion, social influence, financial satisfaction, and attitudes towards awareness of Islamic financial planning among students at University Malaysia Kelantan (UMK). The sample consisted of 341 students. The sampling method used in this study is a non-probability sampling method that makes convenience sampling an option. Data collection for this study was done by researchers using a "Google Form" distributed online. The findings show that religion (r = 0.739, p = 0.00), social influence (r = 0.511, p = 0.00), financial satisfaction (r = 0.407, p = 0.00), and attitude (r = 0.394, p = 0.00) are factors that have a significant relationship with the level of awareness of Islamic financial planning. The results of the analysis confirm that there is a significant positive correlation between religion, social influence, financial satisfaction, attitude, and awareness of Islamic financial planning. In addition, this study has several limitations. Therefore, some suggestions are put forward for future research.